Frequency and Pattern of Anomalous Origin of Coronary Artery in Bangladeshi Population: Coronary Angiogram Based Single Center Study - Anwar, AFM Azim; Rana, Masud; Hashan, Md Nazmul; Alam, Md Khurshid; Tirtho, Srizon Roy; Mumu, Sanjida Anjum; Khaled, Md Fakhrul Islam; Ahmed, Chaudhury Meshkat (Bangladesh Heart Journal, 2024)
Background: Anomalous origin of coronary artery (AOCA) has been traditionally described by coronary angiography or autopsy. However the actual prevalence of such abnormalities is unknown in general Bangladeshi population. Beside conventional coronary angiogram(CAG), CT CAG and Multi-detector computed tomography (MDCT) offers higher possibility to visualize AOCA non-invasively. The purpose of this study was to report the prevalence AOCA in Bangladeshi population by using conventional CAG. Methodology: This was a single center, cross sectional, observational study, done in department of Cardiology, BSMMU over 1 year period. Sample size was 1167. Samples were taken following inclusion and exclusion criteria. Descriptive statistical analysis was done by using SPSS v29.0 Results: 1.3% population had AOCA. Commonest (0.6%) was ‘absent Left main (LM) with separate origin of Left Anterior Descending (LAD) and Left Circumflex (LCX) artery. Second commonest (0.45%) was ‘Right Coronary Artery (RCA) arising from left sinus’. 0.17% had RCA highup origin, and 0.08% had RCA origin from posterior sinus. Discussion: Among AOCA, RCA origin from left sinus, is potentially dangerious, due to high risk of sudden cardiac death (SCD) and surgical complications. Other varities of AOCA are mostly benign, but it may cause difficulties in cannulation during coronary angiography and coronary artery bypass surgery. Conclusion: Although coronary artery anomalies are rare, they may cause difficulties during coronary interventions or cardiac surgery and may occasionally result in sudden cardiac death. So, optimum precaution to findout the AOCA is needed during conventional CAG, and if suspicion, CT CAG and MDCT should also be used. (Bangladesh Heart Journal 2024; 39(2): 117-120